COVID-19 symptoms and compliance: The mediating role of fundamental social motives - Liu, Ruoting; Zheng, Xueying; Wang, Ziyu; Zhou, Mingjie; Weng, Jianping; Li, Yan-mei; Chen, Xuefeng (Frontiers in Psychology, 2023)
Background Understanding the compliance of infected individuals and the psychological process underlying compliance during pandemics is important for preventing and controlling the spread of pathogens. Our study investigated whether fundamental social motives mediate the relationship between having infectious disease and compliance. Methods An online survey was conducted in March 2020, during the severe phase of the COVID-19 outbreak in China to collect data from 15,758 participants. The survey comprised self-report questionnaires with items pertaining to current symptoms (COVID-19 symptoms, other symptoms or no symptoms), the Fundamental Social Motive Inventory, and measures of compliance. Correlation analysis, linear regression analysis, and structural equation model were used for data analysis. Results The participants with COVID-19 symptoms had lower levels of compliance than those without symptoms, and their lower compliance was caused by a decrease in disease avoidance (indirect effect = −0.058, 95% CI = [−0.061, −0.056]) and familial motives (indirect effect = −0.113, 95% CI = [−0.116, −0.062]). Whereas exclusion concern (indirect effect = 0.014, 95% CI = [0.011, 0.017]) suppressed the effects of COVID-19 symptoms on compliance, the effect disappeared in the multiple mediation model, while those of disease avoidance and familial motives remained. Conclusion Our findings emphasize the critical role of disease avoidance and familial motives in promoting compliance with public health norms during pandemics and suggest that enhancing these motives may serve as an effective intervention strategy to mitigate noncompliance among potentially infected individuals.